Edukasi Gizi Seimbang Anak Pada Ibu sebagai Upaya Pencegahan Masalah Gizi - Agustiana, Dede Irma; Risty, Septi Amalia; Matahelumual, Michelle Miranda Elizabeth; Maul’lana, Muhammad Ilham; Anandhita, Naila Kamila; Septi, Agnes Eka (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Child malnutrition, including undernutrition and stunting, remains a significant public health issue in Indonesia, affecting children’s physical growth and cognitive development. Limited maternal knowledge regarding balanced nutrition principles contributes to suboptimal feeding practices at home. This community service activity aims to analyze the effectiveness of balanced nutrition education for mothers as a strategy to prevent child malnutrition. The method employed was a literature review of five relevant and recent community service journal articles. The review process included article searching, selection based on inclusion criteria, data extraction, and descriptive-qualitative synthesis. The findings indicate that balanced nutrition education consistently improves mothers’ knowledge and awareness, enhances attitudes toward child nutrition, and promotes healthier feeding practices. Long-term impacts include improved dietary patterns and contributions to stunting prevention. Therefore, nutrition education for mothers is an effective community service strategy with the potential to generate sustainable behavioral changes in supporting child nutritional status.